The client - Grisham, John , 1955- (Bantam Dell, 1993)
"... Eleven-year-old Mark Sway and his younger brother ... chance encounter with a suicidal lawyer left Mark knowing a bloody and explosive secret: the whereabouts of the most sought-after dead body in America."-- Colophon